Kebijakan Outsourcing di Indonesia: Perkembangan dan Permasalahan - Asep Ahmad Saefuloh (Jurnal Ekonomi & Kebijakan Publik, 2011)
Over the past two decades, the phenomenon of outsourcing of labours andactivities has emerged as an important trend in a wide range oforganizations across the globe, including those in Indonesia. The legalframework that becomes base of outsourcing is UU No.13 Tahun 2003tentang Ketenagakerjaan (Law No.13/2003 of Labour), although thereinthere’s no definition of outsourcing. The regulation for implementation ofoutsourcing is UU No. 13 Tahun 2003 tentang Ketenagakerjaan (Decree ofMan Power Ministry No.101/2004). A review of practise of outsourcing inIndonesia has found out some problems, such as minimum protection forlabours on some firms. The paper recommended to amend UU No.13Tahun 2003 tentang Ketenagakerjaan (Law No.13/2003 of Labour).